2022
DOI: 10.1371/journal.pone.0264257
|View full text |Cite
|
Sign up to set email alerts
|

Fear among Syrians: A Proposed Cutoff Score for the Arabic Fear of COVID-19 Scale

Abstract: COVID-19 pandemic has led to psychological health issues one of which is fear. This study validates the Arabic version of the fear of COVID-19 scale and suggests a new cutoff score to measure fear of COVID-19 among the Syrian Population. A total of 3989 participants filled an online survey consisting of socio-demographic information, the fear of COVID-19 scale, the patient health questionnaire 9-item, and the generalized anxiety disorder 7-item. Receiver operating characteristic analysis was used to define cut… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…Some studies reported a higher rate of depression and anxiety in healthcare workers than the general population [ 54 56 ], and the FCV-19S scores predicted risk for depression and anxiety [ 32 , 57 ]. Koiwa et al [ 2 ] reported that Japanese nurses scored higher on the FCV-19S compared to nurses in other countries, and while they said it was not possible to compare the scores between each study, their mean was higher than some proposed FCV-19S cutoff values [ 7 , 58 ]. In the present study, the percentage of nurses with anxiety scores higher than the HADS cutoff was about 30% of the total number of nurses; further, the percentage of those with depression scores exceeding the cutoff was 20% of the total number of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported a higher rate of depression and anxiety in healthcare workers than the general population [ 54 56 ], and the FCV-19S scores predicted risk for depression and anxiety [ 32 , 57 ]. Koiwa et al [ 2 ] reported that Japanese nurses scored higher on the FCV-19S compared to nurses in other countries, and while they said it was not possible to compare the scores between each study, their mean was higher than some proposed FCV-19S cutoff values [ 7 , 58 ]. In the present study, the percentage of nurses with anxiety scores higher than the HADS cutoff was about 30% of the total number of nurses; further, the percentage of those with depression scores exceeding the cutoff was 20% of the total number of nurses.…”
Section: Discussionmentioning
confidence: 99%
“…31 The optimized cutoff score was accepted as 17.5, and it was determined that participants with high scores had high COVID-19 fear levels. 35…”
Section: Methodsmentioning
confidence: 99%
“…Total scores range from 7 to 35, with higher scores indicating higher levels of COVID-19-related fear. A cut-off of 17.5 indicates high fear level [ 17 ] and was adopted for this study. In previous research, Cronbach’s α values were found to be 0.82, which demonstrated good internal reliability [ 16 ].…”
Section: Methodsmentioning
confidence: 99%